The Effect of Role Playing Method on Student Learning Outcomes in Social Studies Lessons in Grade IV Elementary School - Manan Manan*; Fazman Fazman; Kamarudin Kamarudin (Riwayat: Educational Journal of History and Humanities, 2023)
The Effect of Role Playing  Method on Student Learning Outcomes in Social Studies Lessons in Grade IV Elementary School. The goal to be achieved by the researcher is to determine the influence of the role playing  method on student learning outcomes in social studies lessons in grade IV SD Negeri 2 Talaga Raya, Talaga Raya District, Central Buton Regency. The data collection method in this study used observation, tests and documentation. The research instrument is in the form of validity of learning outcomes tests and validity of observation sheets. The data analysis techniques used are descriptive and learning outcomes. The results showed that there was a significant influence on the learning outcomes of experimental class students who received special treatment  with the Role Playing method  compared to classes that were treated with regular learning using varied lectures. The results of affective observations in the experimental class were in the score range of 18.71 which means it was in the high category and the control class was in the score range of 11.9 which means it was in the low category. The experimental class obtained an average improvement in learning outcomes of 19.1 while the learning outcomes in the control class increased by an average of 9.35.